Explanation:
= - 4
= a* + (3- 1) d*
- 4 = a + 2d . . . . . . . . .(i)
= - 29
= a + ( 8 - 1) d
- 29 = a + 7d . . . . . . . . (ii)
subtracting equations (i) and (ii)
25 = 5d
d = -5
placing d = -5 in equation (i)
a - 10 = -4
a = 6
For an arithmetic Progtession
= a + (n - 1)d
= 6 + (n- 1)-5
= 6 - 5n + 5
![\underline {a_n = 11 - 5n }](https://img.qammunity.org/2022/formulas/mathematics/college/sfqbc9q6qcavckxg6lvoaimkqpw0j95xrl.png)
![\\](https://img.qammunity.org/2022/formulas/mathematics/college/unelomwtwf38bcxnumqigvvzlkm3cxs2u0.png)
*
![\boxed{ \mathfrak { a \:stands\: for\: first\: term } }](https://img.qammunity.org/2022/formulas/mathematics/college/855aa2e2eaui13j0ps8ynzb4c4g9xiqisr.png)
*
![\boxed{ \mathfrak { d \:stands\: for\: common \: difference } }](https://img.qammunity.org/2022/formulas/mathematics/college/wzs2q5u99mp5axntsmm3pd1zdza6suh8hz.png)